Cavernous Malformations of the Brainstem Presenting in Childhood: Surgical Experience in 40 Patients - Abla, Adib A; Lekovic, Gregory P; Garrett, Mark; Wilson, David A; Nakaji, Peter; Bristol, Ruth; Spetzler, Robert F (Neurosurgery, 2010)
Abstract BACKGROUND: Brainstem cavernous malformations (BSCMs) are believed to compose 9% to 35% of all cerebral cavernous malformations, but these lesions have been reported in children in very limited numbers. OBJECTIVE: To review surgical outcomes of pediatric patients with BSCMs treated at 1 institution. METHODS: We retrospectively analyzed the course of 40 pediatric patients (19 males, 21 females; age range, 10 months to 18.9 years; mean, 12.3 years) who underwent surgery between 1984 and 2009. Age, sex, presenting symptoms, location of lesion, surgical approach, new postoperative deficits, Glasgow Outcome Scale score, recurrences, and resolution of baseline symptoms were recorded. RESULTS: Thirty-nine patients experienced hemorrhage before surgery. Lesion locations included the pons (n = 22), midbrain (n = 4), midbrain and thalamus (n = 4), pontomesencephalic junction (n = 3), medulla (n = 3), pontomedullary junction (n = 3), and cervicomedullary junction (n = 1). Mean lesion size was 2.3 cm. Mean length of hospital stay was 10.7 days. The average clinical follow-up was 31.9 months in 36 patients with follow-up after discharge. At last follow-up, 5 patients had experienced symptoms and/or imaging consistent with rehemorrhage, either from a residual that enlarged or true recurrence (5.25% annual rebleed risk per patient after surgery); 2 required reoperation for further resection of cavernoma. Mean Glasgow Outcome Scale score was 4.2 on admission, 4.05 at discharge, and 4.5 at latest follow-up. Preoperative symptoms and deficits improved in 16 patients (40%). New neurological deficits developed in 19 patients (48%) and resolved in 9, leaving 10 patients (25%) with new permanent deficit. CONCLUSION: Compared with adults, pediatric patients with BCSMs tend to have larger lesions and higher rates of recurrence (regrowth of residual lesion). Given the greater life expectancy of children, surgical treatment seems warranted in those with surgically accessible lesions that have bled. Outcomes were similar to those in our adult series of patients with BSCMs.